2008
DOI: 10.1177/1073858408322675
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic NMDA Receptors: Newly Appreciated Roles in Cortical Synaptic Function and Plasticity

Abstract: Many aspects of synaptic development, plasticity, and neurotransmission are critically influenced by NMDA-type glutamate receptors (NMDARs). Moreover, dysfunction of NMDARs has been implicated in a broad array of neurological disorders, including schizophrenia, stroke, epilepsy, and neuropathic pain. Classically, NMDARs were thought to be exclusively postsynaptic. However, substantial evidence in the last 10 years demonstrates that NMDARs also exist presynaptically, and that presynaptic NMDA receptors (preNMDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
159
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(175 citation statements)
references
References 112 publications
14
159
0
2
Order By: Relevance
“…Moreover, blockade of DOI-elicited potentiation of NMDA currents by ifenprodil showed involvement of GluN2B-containing NMDA receptors. Although NMDA receptors were classically considered as postsynaptic receptors, increasing evidence indicates that they are also expressed presynaptically, and that up-regulation of presynaptic NMDA receptors enhances the probability of spontaneous and evoked neurotransmitter release at cortical, hippocampal, and cerebellar synapses (53). Moreover, the GluN2B subunit has been identified as one of the subunits of cortical presynaptic NMDA receptors (53), an observation confirmed in the present study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, blockade of DOI-elicited potentiation of NMDA currents by ifenprodil showed involvement of GluN2B-containing NMDA receptors. Although NMDA receptors were classically considered as postsynaptic receptors, increasing evidence indicates that they are also expressed presynaptically, and that up-regulation of presynaptic NMDA receptors enhances the probability of spontaneous and evoked neurotransmitter release at cortical, hippocampal, and cerebellar synapses (53). Moreover, the GluN2B subunit has been identified as one of the subunits of cortical presynaptic NMDA receptors (53), an observation confirmed in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…Although NMDA receptors were classically considered as postsynaptic receptors, increasing evidence indicates that they are also expressed presynaptically, and that up-regulation of presynaptic NMDA receptors enhances the probability of spontaneous and evoked neurotransmitter release at cortical, hippocampal, and cerebellar synapses (53). Moreover, the GluN2B subunit has been identified as one of the subunits of cortical presynaptic NMDA receptors (53), an observation confirmed in the present study. Collectively, these findings strongly support a mechanism whereby the activation of presynaptic 5-HT 2A receptors expressed on thalamocortical afferents might locally induce, via PKC, the phosphorylation of presynaptic GluN2B-containing NMDA receptors.…”
Section: Discussionsupporting
confidence: 83%
“…Because our studies also reveal enhancement in presynaptic NMDAR-mediated glutamate release in these enlarged boutons, the potential consequences of α7 blockade may include a variety of downstream events, such as alteration of postsynaptic transmission and synaptic strength (16). Immunocytochemical studies revealed the presence of NR1, NR2 and GluR1 subunits in the enlarged glutamatergic presynaptic boutons.…”
Section: Discussionmentioning
confidence: 59%
“…Presynaptic NMDARs have recently been implicated in cortical synaptic function and plasticity (16). They exist at higher levels early in development, and are involved in regulation of transmitter release and forms of LTD (16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…PreNMDARs also mediate diverse forms of LTP and LTD at subsets of synapses, including timing-dependent LTD at cortical synapses and theta-burst stimulation induced corticalstriatal LTP [45,[64][65][66]. PreNMDARs are therefore likely to bias plasticity and circuit modifica-tion.…”
Section: Synapse-type-specific Long-term Plasticitymentioning
confidence: 99%